Recurrence of multicystic ameloblastoma: case report (Revista da Faculdade de Odontologia - UPF, 2016)
Introduction: The WHO classifies ameloblastoma as abenign epithelial odontogenic tumor without odontogenicectomesenchyme with locally invasive behaviorand high recurrence rate. It represents 1% of oral tumors,primarily affecting the posterior mandible. Generallyslow growing and asymptomatic, it can perforatethe cortical bone, reabsorb and move teeth, and causefacial asymmetry. Classification may be given, accordingto clinical and radiographic aspects, as solid ormulticystic, cystic, and peripheral ameloblastoma. Objectives:To report a case of multicystic ameloblastomatreated with marginal resection of the mandible. Casereport: 34-year-old patient referred for assessment ofmultiloculated radiolucent lesion involving areas of thebody, angle, and right mandibular ramus, revealing byhistopathological examination the diagnosis of ameloblastoma.The patient underwent resection surgery andreconstruction plate fixation for layer maintenance. Eighteenmonths after surgery, there were no clinical orradiographic signs. Final considerations: The interpretationof clinical and imaging data of patients with ameloblastomais essential for early diagnosis and effectivetreatment of the lesion. Follow-up with regular visits isan essential part of treatment, considering their local aggressivenessand high recurrence rate.